Pemodelan Jalur pada Faktor yang Mempengaruhi Kriminalitas di Sulawesi Selatan Tahun 2021 - Sukarna; Ahmad Zaki; Muh. Ilham (Universitas Islam Negeri Alauddin Makassar, 2022)
South Sulawesi has many diverse track records in criminal acts, including theft. The causal factors of crime should be detected and found scientifically to assist professionally and academically all parties in reducing or avoiding the consequences or increasing crime. The study purpose is to create the model crime (especially theft) in South Sulawesi based on the factors that influence it. The model is path analysis which is able to determine direct and indirect effects. Data obtained from BPS South Sulawesi in the form of population, education, poverty, unemployment, crime. Two models are presented to provide recommended solutions that the population, education, poverty and unemployment affect the crime rate. The dominant variable that directly affects crime is the population of 2,149 and the smallest influence is education of 0.158 Keywords: Path analysis, population, unemployment, crime